Can Beauveria bassiana (Bals.-Criv.) Vuill. control the key fruit pests of the european chestnut tree, under field conditions? - Souza, Maria Eliza Cota e (2015)
Simple Summary Portugal has the largest chestnut tree plantation area for fruit production in Europe. The carpophagous pests Cydia splendana Hubner and Curculio elephas Gyllenhal are among the main pests that affect nut productivity and quality in the country. Their control is considered difficult due to the large size of the trees, and chestnut orchards are mostly located in mountain regions with high slopes. On the other hand, the biology of the insects, which spend most of their life cycle inside the fruit or buried in the ground, is an aspect that makes them difficult to control. Entomopathogenic fungi are considered safe biological organisms for the environment and capable of regulating the natural population of pests. Beauveria bassiana (Bals.-Criv.) Vuill. is one of the most used for this purpose; however, its effectiveness is highly influenced by environmental factors. The study aimed to investigate the efficiency of B. bassiana in controlling these two carpophagous pests under environmental conditions. The fungus could infect and kill C. splendana and C. elephas larvae under the two conidial concentrations tested, showing favorable results for its use in the biocontrol of these insects. The chestnut moth (Cydia splendana Hubner) and the chestnut weevil (Curculio elephas Gyllenhal) cause serious damage to European producers and companies that transform and market the chestnut. The objective of the present work was to evaluate, under field conditions, the possibilities of Beauveria bassiana (Bals.-Criv.) Vuill. to infect and kill the larvae of the two main carpophagous pests of European chestnut, in treatments directed at the soil. For this purpose, the surfaces of vases were sprayed with two concentrations of conidia/mL 5 x 10(7) (T1) and 1 x 10(8) (T2). The control (T0) was sprayed with distilled water. Larval mortality and infection were evaluated on five dates (D8 to D220). Confirmation of the fungus present in the larva was performed by molecular analysis. The results obtained are promising for the use of B. bassiana as a biological control agent against these key pests of the chestnut crop. There were no significant differences in mortality between the T1 and T2 modalities, however, they were significantly higher than the control. In the case of total mortality (dead and infected larvae), no significant differences were observed for C. elephas either. In the case of C. splendana, the T2 modality obtained better results in terms of total mortality.